PENGGUNAAN OFF-LABEL DRUG PADA PASIEN GERIATRI DENGAN PENYAKIT DEGENERATIF DI APOTEK WILAYAH SURAKARTA - Nila Darmayanti Lubis; Santi Dwi Astuti (Fakultas Farmasi Universitas Setia Budi, 2021)
ABSTRACT Off-label drug use in geriatric patients who have degenerative diseases has the potential to cause medication errors or adverse drug reactions but off-label is not always bad and harmful. The purpose of this study was to determine the prevalence of off-label drug use in the categories of indication, dosage, contraindication and age in geriatric patients with degenerative diseases. This study used a descriptive design. Data were collected by retrospectively. Samples were taken with a purposive sampling technique from several Pharmaceutical Installation in the Surakarta that served prescriptions with inclusion criteria for geriatric patients with degenerative diseases, prescriptions were written by specialists, prescriptions were redeemed at pharmacies that had collaborated with specialist doctors, prescriptions that had complete information, prescriptions that entered the pharmacy in April-May 2019 and matched the information on the use of the drug with the medicine leaflet. The evaluation results of the use of off-label drugs in geriatric patients with degenerative diseases in pharmacies in the Surakarta region are the prevalence of the use of off-label drug indicative categories of 7.6%; the prevalence of off-label drug use in the dose category is 33.92%; the prevalence of off-label drug use is contraindicated and age category is 0%.